PENGARUH KETERBUKAAN DIRI TERHADAP INTIMASI PERTEMANAN PADA MAHASISWA KOMUNIKASI DAN PENYIARAN ISLAM DI IAI AL-AZIS - Nur Allifah, Shalma; Nurkholis Abdurrazaq, Muhammad; Asrof Fitri, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students in the Islamic Communication and Broadcasting Study Program are required to have good communication skills, but it is not yet known how self-disclosure affects the intimacy of their friendships. This study aims to analyze the effect of self-disclosure on friendship intimacy among students in the Islamic Communication and Broadcasting Study Program at IAI AL-AZIS. The method used is quantitative associative with a survey approach, using a Likert scale questionnaire adapted from the theory of Jourard and DeVito (self-disclosure) and the conceptual framework of Sharabany (friendship intimacy). The sample consisted of 59 students selected through simple random sampling. Data analysis used simple linear regression testing with the help of SPSS version 25. The results showed that self-disclosure had a significant effect on friendship intimacy with a coefficient of determination of 68.8%, indicating a very strong positive relationship. The remaining 31.2% was influenced by other factors outside the model. The study concluded that self-disclosure is an important predictor in building friendship intimacy. The implication is that developing programs that support self-disclosure can improve the quality of interpersonal relationships in academic settings.